Using low carbon footprint high-pressure carbon dioxide in bioconversion of aspen branch waste for sustainable bioethanol production. (October 2020) - Wu, Yingji; Ge, Shengbo; Xia, Changlei; Cai, Liping; Mei, Changtong; Sonne, Christian; Park, Young-Kwon; Kim, Young-Min; Chen, Wei-Hsin; Chang, Jo-Shu; Lam, Su Shiung
Graphical abstract: Highlights: High-pressure CO2 applies to hydrolysis-fermentation of waste aspen branch chips. The hemicellulose content dramatically reduces from 19.7% to 1.6%. The pore area and porosity significantly increase for adsorbing more enzymes. High yield of glucose (82.9%) with 10.0% increase in bioethanol is obtained. Energy consumption and production cost of bioethanol reduce by 35% and 44%. Abstract: An innovative approach was developed by incorporating high-pressure CO2 into the separate hydrolysis-fermentation of aspen leftover branches, aiming to enhance the bioethanol production efficiency. The high-pressure CO2 significantly increased the 72-h enzymatic hydrolysis yield of converting aspen into glucose from 53.8% to 82.9%. The hydrolysis process was performed with low enzyme loading (10 FPU g −1 glucan) with the aim of reducing the cost of fuel bioethanol production. The ethanol yield from fermentation of the hydrolyzed glucose using yeast ( Saccharomyces cerevisiae ) was 8.7 g L –1, showing increment of 10% compared with the glucose control. Techno-economic analysis indicated that the energy consumption of fuel bioethanol production from aspen branch chips was reduced by 35% and the production cost was cut 44% to 0.615 USD L –1, when 68 atm CO2 was introduced into the process. These results furtherly emphasized the low carbon footprint of this sustainable energy production approach.